2010
DOI: 10.1186/1479-5876-8-45
|View full text |Cite
|
Sign up to set email alerts
|

CCL20/CCR6 expression profile in pancreatic cancer

Abstract: BackgroundCCL20 and its receptor CCR6 have been shown to play a role in the onset, development and metastatic spread of various gastrointestinal malignancies. In this study, the expression profile and clinical significance of the CCL20/CCR6 system in distinct benign, pre-malignant and malignant pancreatic tissues was investigated.MethodsUsing RealTime-PCR, enzyme-linked immunosorbent assay (ELISA), Western Blot and immunohistochemistry, we have analyzed the expression profile of CCL20/CCR6 in resection specime… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
42
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 58 publications
(46 citation statements)
references
References 38 publications
3
42
0
1
Order By: Relevance
“…(Mrizak et al , 2015) CCL20 is certainly up-regulated in PDAC tissue at both the mRNA and protein level although whether this is secreted in exosomes is still to be determined. (Rubie et al , 2010) IL-2 is a key regulator of the proliferation and differentiation of a variety of innate immune cell subsets including CD8 + T-Cells, NK cells and Tregs. (Boyman et al , 2015) Clayton et al have demonstrated that exosomes derived from a variety of tumour cell lines inhibit the IL-2 induced proliferation of predominantly CD4 + T-Cells although this effect was not seen on CD4 + FOXP3 + Treg cells.…”
Section: Exosomes and The Adaptive Immune Response To Pdacmentioning
confidence: 99%
“…(Mrizak et al , 2015) CCL20 is certainly up-regulated in PDAC tissue at both the mRNA and protein level although whether this is secreted in exosomes is still to be determined. (Rubie et al , 2010) IL-2 is a key regulator of the proliferation and differentiation of a variety of innate immune cell subsets including CD8 + T-Cells, NK cells and Tregs. (Boyman et al , 2015) Clayton et al have demonstrated that exosomes derived from a variety of tumour cell lines inhibit the IL-2 induced proliferation of predominantly CD4 + T-Cells although this effect was not seen on CD4 + FOXP3 + Treg cells.…”
Section: Exosomes and The Adaptive Immune Response To Pdacmentioning
confidence: 99%
“…In pancreatic adenocarcinoma (PAC) patients, CCL20 mRNA and protein expression was found to be significantly associated with advanced T-stage [154] . It is interesting that CCR6, a canonical CCL20 receptor, is upregulated in chronic pancreatitis, pancreatic cystadenoma and pancreatic carcinoma compared to controls [154] . It has also been reported that, in metastatic pancreatic carcinoma, expression of the angiogenic chemokines CXCL5 and CXCL8 is highly elevated compared to pancreatic cystadenoma or chronic pancreatitis [138] .…”
Section: Pancreasmentioning
confidence: 99%
“…Upregulated in chronic pancreatitis, pancreatic cystadenoma and pancreatic carcinoma [154] CXCL5, CXCL8…”
Section: Ccr6mentioning
confidence: 99%
See 1 more Smart Citation
“…In our previous studies, the role of certain chemokines was outlined in distinct gastrointestinal tumors, such as hepatocellular carcinoma, and pancreatic and colorectal cancer (7)(8)(9). Chemokine receptors are linked to seven-transmembrane heterotrimeric G proteins and divided into the chemokine (C-X-C motif) receptor (CXCR) and the chemokine (C-C motif) receptor �CCR�, which mediate a range of pro� and anti�inflammatory responses through the interaction with the two major CXC and CC subfamilies of chemokines, respectively (10).…”
Section: Introductionmentioning
confidence: 99%